Analisis Dampak Sistem Penilaian Diri Dan Pemeriksaan Pajak Terhadap Penerimaan Pajak Penjualan (PPN) Di Kantor Pajak Pratama Mulyorejo: Studi Kasus Tahun 2020-2022 - Joys Oktavia Santoso; Hwihanus Hwihanus (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
The state's contribution from taxes amounts to 85%, indicating the dominant role of taxes in significantly contributing to the state's finances. This research aims to examine the influence of the self-assessment system and tax audits on the Value Added Tax (VAT) revenue. The self-assessment system emphasizes the active role of taxpayers in fulfilling their tax obligations; however, the potential for taxpayer non-compliance may negatively impact tax revenue. Therefore, tax audits are essential to balance the implementation of the self-assessment system and ensure that the filing of Tax Returns (SPT) aligns with the conditions of the taxable objects. This study employs a quantitative method with descriptive analysis. Data analysis involves multiple linear regression and testing classical assumptions such as multicollinearity, autocorrelation, normality, and heteroskedasticity. Hypothesis testing is conducted using t-tests and F-tests with the assistance of SPSS 22. A sample of 36 respondents was selected based on specific criteria, and secondary data were obtained from the Mulyorejo Primary Tax Office in the form of documents. The research findings indicate that simultaneously, the self-assessment system and tax audits do not significantly influence VAT revenue in the Mulyorejo Primary Tax Office during the period of 2020-2022. The implication is that while the active role of taxpayers and tax audits has potential impacts, their simultaneous implementation does not significantly contribute to the increased Value Added Tax revenue in the region.